Chronic effects of different resistance training exercise orders on flexibility in elite judo athletes - Saraiva, A. R.; Reis, V. M.; Costa, P. B.; Bentes, C. M.; Costa e Silva, G. V.; Novaes, J. S. (Journal of Human Kinetics, 2014)
The aim of this study was to examine the effects of twelve weeks of resistance training with different exercise orders (upper limbs and lower limbs vs. lower limbs and upper limbs) on flexibility levels in elite judo athletes. Thirtynine male athletes were randomly divided into 3 groups as follows: G1 (n = 13), G2 (n = 13), and CG (n = 13). The flexibility was assessed on 8 joint movements: shoulder flexion and shoulder extension, shoulder abduction and shoulder adduction, trunk flexion and trunk extension, and hip flexion and hip extension. Two-way repeated measures ANOVAs (time [pre-experimental vs. post-experimental] × group [G1 vs. G2 vs. CG]) were used to compare the differences between pre- and post-test situations and the differences among groups. The results from the within-group (pre vs. post) comparisons demonstrated significant increases (p < 0.05) in the range of motion of 3.93 and 5.96% for G1 and G2 training groups, respectively, in all joints. No significant changes (p > 0.05) were observed for the CG. The results from the between-group comparisons demonstrated no significant differences (p > 0.05) in the range of motion between G1post vs. G2post (1.15%). Although both exercise orders (from upper to lower limbs and from lower to upper limbs) increased flexibility, no significant variations were observed between the different exercise orders. Nevertheless, these findings demonstrate that flexibility gains could be obtained with a resistance training program, and thus, more time can be devoted to sports-specific judo training.